1986
DOI: 10.1126/science.3952506
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Overproduction of Synapses in Diverse Regions of the Primate Cerebral Cortex

Abstract: Synapses develop concurrently and at identical rates in different layers of the visual, somatosensory, motor, and prefrontal areas of the primate cerebral cortex. This isochronic course of synaptogenesis in anatomically and functionally diverse regions indicates that the entire cerebral cortex develops as a whole and that the establishment of cell-to-cell communication in this structure may be orchestrated by a single genetic or humoral signal. This is in contrast to the traditional view of hierarchical develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
587
6
6

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,065 publications
(650 citation statements)
references
References 34 publications
51
587
6
6
Order By: Relevance
“…One account has to do with the loss of neural plasticity due to massive pruning of synapses and brain cells during childhood (e.g., Rakic, Bourgeois, Zecevic, Eckenhoff, & Goldman-Rakic, 1986), rendering language learners less able to make use of relevant input later in life. Another account has to do with early language experience setting fundamental parameters in the Universal Grammar, thereby heavily influencing subsequent language acquisition (e.g., Chomsky, 1981; see also Pinker, 1994, on both accounts).…”
Section: Discussionmentioning
confidence: 99%
“…One account has to do with the loss of neural plasticity due to massive pruning of synapses and brain cells during childhood (e.g., Rakic, Bourgeois, Zecevic, Eckenhoff, & Goldman-Rakic, 1986), rendering language learners less able to make use of relevant input later in life. Another account has to do with early language experience setting fundamental parameters in the Universal Grammar, thereby heavily influencing subsequent language acquisition (e.g., Chomsky, 1981; see also Pinker, 1994, on both accounts).…”
Section: Discussionmentioning
confidence: 99%
“…Various data [21] have shown that in early life, the brain initially has a large number of synapses that undergo a period of intense dying off (at approximately 6 -12 years in humans). It is thought that the selection process that determines which synapses are maintained and which ones are eliminated takes place by competitive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Another event that does not fit the model is a coordinated surge in synaptogenesis, an event apparently linked just prior to an onslaught of experience. This phenomenon begins just prior to birth in primates and just prior to exit from the nest in rats (Bates et al, 2002;Blue and Parnavelas, 1983;Huttenlocher and Dabholkar, 1997;Rakic et al, 1986;Zecevic and Rakic, 1991). A similar link to birth is found in some respiratory, cardiovascular and digestive functions, linked to the demands of extrauterine survival.…”
Section: Exceptions and Limitationsmentioning
confidence: 93%